Active transport of cytoophidia in Schizosaccharomyces pombe. Issue 11 (21st May 2018) - Li, Hui; Ye, Fangfu; Ren, Jing-Yi; Wang, Peng-Ye; Du, Li-Lin; Liu, Ji-Long
ABSTRACT: The metabolic enzyme cytidine triphosphate synthase has recently been found to form micrometer‐sized filamentous structures termed cytoophidia, which are evolutionarily conserved across prokaryotes and eukaryotes. The cytoophidium represents a novel type of membraneless organelle and behaves dynamically inside the cell. The question of how cytoophidia transport is mediated, however, remains unanswered. For the first time, we detected in this study the active transport of cytoophidia, taking advantage of the fission yeast Schizosaccharomyces pombe as an excellent model for studying membraneless organelles. We demonstrated that actin filaments, not microtubules, are responsible for this transport. Furthermore, we determined that Myo52, a type of myosin V, is required for the active transport of cytoophidia. These results reveal the major players critical to the dynamics of cytoophidia and extend our understanding of in tracellular transport of membraneless organelles.—Li, H., Ye, F., Ren, J.‐Y., Wang, P.‐Y., Du, L.‐L., Liu, J.‐L. Active transport of cytoophidia in Schizosaccharomyces pombe. FASEB J. 32, 5891–5898 (2018). www.fasebj.org